Disruption of ASN Behavior in Bali: Challenges and Obstacles towards Smart ASN - Jayendra, Anak Agung Ngurah; Darma, Gede Sri (Budapest International Research and Critics University, 2022)
Indonesia is entering the digitalization era of industry 4.0 and also the COVID-19 pandemic which demands the performance of the State Civil Apparatus to transform towards Smart ASN. Disruption changes the order of ASN performance, becoming more adaptive with the use of information and telecommunications technology. Smart ASN is a program that is expected to be a solution in responding to obstacles and challenges in the era of globalization. This study examines the readiness, challenges and obstacles of ASN at the Bali Provincial Education, Youth and Sports Office in realizing Smart ASN. This study uses qualitative methods with observation, documentation and interview techniques. The results of this study indicate that the Bali Province Disdipora is ready to realize Smart ASN. ASN readiness can be seen from the performance of ASN Disdipora which has been adaptive with IT-based applications in improving the quality of public services. Utilization of IT-based applications is very significant in supporting the performance of ASN, but digital competence is not evenly distributed and is still low, as well as sudden application changes are obstacles faced by ASN in optimizing efforts to realize Smart ASN.